Pelatihan Pengaplikasian POC Limbah Nanas bagi Paguyuban PK-5 Sukowono untuk Mendukung Pertumbuhan Vegetatif Tanaman Pakan Kupu di Irenggolo Kediri - Sulistiyowati, Tutut Indah; Utami, Budhi; Mahardika, Monicha Shinta; Annafinurika, Mukhammad; Setyana, Putri Eka Wahyu; Ulfa, Dian Anita (Universitas Nusantara PGRI Kediri, 2022)
The daily manager of the Irenggolo Kediri tourist area is a group of residents who are members of PK-5. Based on the results of observations and interviews, it is known that the residents do not know the application of liquid organic fertilizer (POC) and how to make it. The purpose of this activity is to increase the skills of residents in processing waste into fertilizer, as well as being able to apply it to existing plants. The method of implementing this activity is divided into two, namely socialization about the application of POC and the role of plants for the ecosystem; as well as demonstrations of making POCs and training in their application. The results of this activity are in the form of products (1.8 liters of POC pineapple waste from the fermentation process) and the skills of residents in applying POC. As many as 75% of residents can apply POC correctly, and 55% of residents begin to design household waste processing into POC. So it can be concluded that this activity can improve the knowledge and skills of residents.